2019
DOI: 10.1002/ece3.5076
|View full text |Cite
|
Sign up to set email alerts
|

Predatory lizards perceive plant‐derived volatile odorants

Abstract: Many lizards are olfactory foragers and prey upon herbivorous arthropods, yet their responses to common herbivore‐associated plant volatiles remain unknown. As such, their role in mediating plant indirect defenses also remains largely obscured. In this paper, we use a cotton‐swab odor presentation assay to ask whether lizards respond to two arthropod‐associated plant‐derived volatile compounds: 2‐( E )‐hexenal and hexanoic acid. We studied the response of two lizard species, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…The active foraging lizard (Sceloporous virgatus) responds to the GLV (E)-2-hexenal primarily by inducing tongue-icking, which is a known chemosensory behavior. 218 Apart from this example, little is known about the impact of plant volatiles on reptiles. 218,219 Several herbivorous mammals are known to use vegetative plant volatiles as foraging cues.…”
Section: Effects On Vertebrates Including Humansmentioning
confidence: 99%
See 2 more Smart Citations
“…The active foraging lizard (Sceloporous virgatus) responds to the GLV (E)-2-hexenal primarily by inducing tongue-icking, which is a known chemosensory behavior. 218 Apart from this example, little is known about the impact of plant volatiles on reptiles. 218,219 Several herbivorous mammals are known to use vegetative plant volatiles as foraging cues.…”
Section: Effects On Vertebrates Including Humansmentioning
confidence: 99%
“…218 Apart from this example, little is known about the impact of plant volatiles on reptiles. 218,219 Several herbivorous mammals are known to use vegetative plant volatiles as foraging cues. Goats respond negatively to terpenes emitted by galls formed during gregarious aphid (Salvum wertheimae) infestation of wild pistachio (Pistacia atlantica) trees.…”
Section: Effects On Vertebrates Including Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…In most animals, both males and females can adjust their foraging behavior to achieve their nutritional goals and to avoid harmful components, often through the same behavioral and neurophysiological adaptations. Examples include increasing locomotion when starved to promote food searching and acquisition ( Zhao et al, 2011 ; Yu et al, 2016 ), and the ability to sense or differentiate potential food sources based on volatile cues released by the food as well as cues released by associated microbes ( Becher et al, 2012 ; Stensmyr et al, 2012 ; Martini et al, 2014 ; Karageorgi et al, 2017 ; Goldberg et al, 2019 ; Kim et al, 2019 ). However, males and females are distinct in their foraging motivation and reproductive investments.…”
Section: Introductionmentioning
confidence: 99%
“…Whiptail lizards (genus Aspidoscelis ) in particular perform a high frequency of chemosensory behaviors both in baseline conditions and when exposed to prey‐associated odors (Baeckens et al., 2017; Cooper et al., 2000), however, few studies have attempted to examine the precise compounds responsible for eliciting prey‐associated chemosensory responses from whiptail lizards. Studies have shown that only insect‐associated chemical cues will elicit a response from actively foraging lizards and that they do not respond to plant‐associated compounds (Cooper, 1997; Cooper et al., 2000)—even those that are associated with herbivorous insects (Goldberg et al., 2019). One study found that lipids and proteins elicit biting by lizards, but that carbohydrates will not (Cooper et al., 2002a); however, this study used chemical cues (pork fat and bovine gamma globulin) that would not be encountered by lizards under natural foraging conditions.…”
Section: Introductionmentioning
confidence: 99%